Determinants of behavioral intention toward telemedicine services among Indonesian Gen-Z and Millenials: A PLS-SEM study on Alodokter application - Eka Pramudita; Hendra Achmadi; Hansa Nurhaida (Journal of Innovation and Entrepreneurship, 2023)
Telemedicine has become increasingly important in healthcare, especially with the COVID-19 pandemic. Despite, Younger generations are more fluent in using technology, previous study shows that older generations (Gen-X) are more satisfied in using telemedicine compared to younger generations. This study aims to identify the factors influencing user satisfaction and behavioral intention toward Alodokter's telemedicine service application usage among Millennials and Gen-Z in Indonesia. A quantitative cross-sectional study was conducted using a purposive sampling technique. A total of 160 Millenials and Gen-Z respondents who had used the Alodokter telehealth application within the past year were chosen in this study. The data were collected by means of an online questionnaire that was distributed through widely used social media platforms. The questionnaire consisted of 30 questions that assessed variables, such as performance expectancy, effort expectancy, social influence, price value, customer satisfaction, and behavioral intention. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software version 3.2.9. The findings reveal that customer satisfaction positively affects behavioral intention. Performance expectancy, effort expectancy, price value, and social influence positively impact customer satisfaction. Price value was shown to have the most positive influence on behavioral intention. This study provides insights into the factors influencing user satisfaction and behavioral intention toward telemedicine service application usage among younger generations in Indonesia. The results can be used to improve telemedicine services and enhance the experience of users, particularly Millennials and Gen-Z.
Keywords: 650; Behavioral intention; Telemedicine; User satisfaction; UTAUT2